Efficacy of Intraoperative Paracetamol and Nefopam Infusions in Addition to Transversus Abdominis Plane Block in Kidney Transplant Recipients - Jaesik Park; Sun Cheol Park; Min Suk Chae; Sang Hyun Hong; Jung-Woo Shim (Medicina)
Background and Objectives: Kidney transplantation (KT) is an important treatment modality for renal failure. However, moderate-to-severe pain often occurs in KT recipients. Multimodal analgesia using combined analgesic measures has been recommended to enhance postoperative recovery. This retrospective study explored the additional analgesic efficacy of paracetamol and nefopam infusions in living-donor KT recipients who received a transversus abdominis plane (TAP) block. Materials and Methods: Consecutive living-donor KT recipients at our institute between January 2020 and March 2022 were divided into groups that received a TAP block with paracetamol and nefopam infusions (Group TA) or a TAP block without analgesics (Group T) during surgery. Following propensity-score (PS) matching, 103 patients were included in each group. Postoperative pain intensity assessed using the visual analog scale (VAS), opioid consumption via patient-controlled analgesia (PCA) devices over 24 h, and postoperative outcomes were compared between the two groups. Results: VAS pain intensity at rest was lower in group TA than in group T at 1 and 6 h after surgery [1 h: 29 (15–41) vs. 41 (29–51) mm, p < 0.001; 6 h: 32 (23–43) vs. 40 (32–54) mm, p < 0.001]. The VAS pain intensity during coughing was lower in group TA [1 h: 46 (30–58) vs. 59 (48–69) mm, p < 0.001; 6 h: 51 (40–63) vs. 60 (45–71) mm, p < 0.001]. Moreover, PCA consumptions during the first 6 h and between 6–24 h post-surgery was significantly lower in group TA. Other postoperative outcomes did not differ between the two groups. Conclusions: Multimodal analgesia with intraoperative paracetamol and nefopam infusions improved postoperative pain control in living-donor KT recipients who received a preoperative TAP block. Our findings demonstrate the efficacy of paracetamol and nefopam infusions in KT recipients.